2016
DOI: 10.1148/radiol.2015141876
|View full text |Cite
|
Sign up to set email alerts
|

T1-weighted Dynamic Contrast-enhanced MR Imaging of the Lung in Asthma: Semiquantitative Analysis for the Assessment of Contrast Agent Kinetic Characteristics

Abstract: The contrast agent kinetic characteristics of T1-weighted DCE MR images of asthmatic lungs are different from those of healthy lungs and are related to measurements of pulmonary function testing but not to eosinophil level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…DCE 1 H-MRI has previously been used to report on lung perfusion defects, [38][39][40] employing T 1 -weighted imaging to monitor GBCA bolus passage through the pulmonary vasculature. The DSC 19 F-MRI approach we present here differs from DCE 1 H-MRI in its ability to report on gas phase PFP directly adjacent to contrast agent that is present within the alveolar microvasculature.…”
Section: Discussionmentioning
confidence: 99%
“…DCE 1 H-MRI has previously been used to report on lung perfusion defects, [38][39][40] employing T 1 -weighted imaging to monitor GBCA bolus passage through the pulmonary vasculature. The DSC 19 F-MRI approach we present here differs from DCE 1 H-MRI in its ability to report on gas phase PFP directly adjacent to contrast agent that is present within the alveolar microvasculature.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to healthy controls, IPF subjects had reduced peak enhancement and k washin , parameters reflective of the microvasculature, in all measured lung regions on unadjusted analyses, and only reductions in k washin in the whole lung, lower axial and posterior coronal regions remained statistically significant when adjusting for age. A reduced first-pass peak, denoting a reduction in peak enhancement and a slower contrast wash-in rate, has been demonstrated in other pulmonary conditions such as COPD and asthma and was rationalised as decreased tissue perfusion and/or contrast agent extravasation from increased vascular permeability [ 8 , 23 ]. It was recently demonstrated by W eatherley et al [ 11 ] that contrast bolus lung transit time increased over time in IPF consistent with worsening perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…From this information, changes in the microvasculature and the extravascular extracellular space can be quantified [ 5 ]. DCE-MRI is widely performed in brain and breast tumour imaging [ 6 , 7 ] and is starting to be applied to pulmonary conditions [ 8 11 ]. Lung MRI has historically been challenging due to motion sensitivity and low signal, but recent MRI advances (radial sampling, sparse sampling, improved reconstruction techniques) enable fast three-dimensional (3D) lung imaging without requiring breath holding or complex registration [ 9 , 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the observed T1 shortening on the second MRI scan performed four (3:41–4:31) hours after the first MRI scan of 3.3(0.3–4.1)% at room air and 1.8(0.1–3.8)% at 100% oxygen (both CF-groups, n = 12) needs to be explained. Recently, a significantly reduced washout of gadolinium-based contrast media in the lung parenchyma was observed using DCE MRI in asthma patients and explained by an increased extravascular space due to interstitial edema or accumulation of fluid within the alveoli and small airways [ 46 ]. Also in a reproducibility study (using 0.1 mmol/kg body weight Gd-DTPA) Triphan et al observed lower T1 values of the lung parenchyma in COPD patients on the second MRI after 23 hours (1124 ms vs 1086 ms; 3,4%)[ 47 ].…”
Section: Discussionmentioning
confidence: 99%